[No smoking ; Advancing science ; Bish [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Focuses on banning smoking in government offices and public places and campaign in support of a Congressional bill banning advertising of cigarettes. Laparoscopy, a new method of surgery that enables doctors to perform operations without "opening up" patients. Pop singer comppser Stephen Bishop in concert with Side A Band.